An Event-Related Potential Study of the Neural Response to Inferred Motion in Visual Images of Varying Coherence - Jia, Lei; Xu, Yufan; Sweeney, John A.; Wang, Cheng; Sung, Billy; Wang, Jun (Frontiers in Psychology, 2019)
A vivid sense of motion can be inferred by viewing static pictures of objects in motion. Similar to perception of real motion (RM), viewing photographs with implied motion (IM) could also evoke activation in the human middle temporal complex (hMT+). Moreover, hMT+ activity also increases in relation to motion coherence. Based on these previous findings, the current study examined whether similar coherence-level dependent activity in hMT+ is seen with IM stimuli across coherence levels. In this study, visual photograph stimuli of a human moving in four directions (left, right, toward, or away from the viewer) was presented to 15 participants. Coherence levels of these stimuli were manipulated by changing the percentage of pictures implying movement in one direction. Electroencephalography data were collected while participants viewed either IM or counterpart non-IM stimuli. The P2 response of bilateral hMT+ substantially increased from low to high coherence level in the IM conditions, but not in the non-IM conditions. This finding demonstrates that hMT+ responses are progressively activated with increasing motion coherence even when motion is inferred, providing novel support for the view that hMT+ activity can be modulated by top-down perceptual influences in addition to its well-established role in processing bottom-up sensory signals.